ANALISIS USAHA PEMBESARAN IKAN NILA DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA DI DESA SUMBERSUKO JAYA BELITANG OKU TIMUR - Sudarti (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this study is to: (1) Calculate the cost, income and income of farmers from the business of nila tilapia in Sumbersuko Jaya Village in Belitang Sub-District, OKU Timur Regency, (2) Knowing the contribution contribution of tilapia farmer income to household income in Sumbersuko Jaya Village, Belitang District, East OKU Regency. This research was conducted in Sumbersuko Jaya Village, Belitang District, East OKU Regency. The selection of the location of this study is determined purposively with the consideration that the village of Sumbersuko Jaya is one of the villages in Belitang sub-district which most of the population is as rice farmers and there are some farmers who do the business of tilapia fish. This research will be conducted in June 2014. This research found that total production cost incurred in the effort of tilapia farming in Sumbersuko Jaya Village Belitang OKU Timur subdistrict is Rp 8.009.219 / Lg / Process, business acceptance of Rp 14.471.696 / Lg / Process so that income received is Rp 6.462.476 / Lg / Process. The value of R / C ratio is 1.8 which indicates that the business of nila tilapia enlargement is beneficial and the contribution of tilapia nil product revenues to total family income in one month is included in medium criterion, with contribution percentage amounted to 39,10%. This is due to the efforts of tilapia fish enlargement is still a side business not as a main business.